2018
DOI: 10.5860/crl.79.3.366
|View full text |Cite
|
Sign up to set email alerts
|

Still a Deadly Disease? Performance Appraisal Systems in Academic Libraries in the United States

Abstract: Performance appraisal of professional librarians in academic libraries is important because of the critical role these employees play. Professional librarians ensure that the library's resources and services are effective, relevant, and integrated within the parent institution. Performance appraisal and job feedback have been understudied in the library literature while, by comparison, these topics have generated great attention in other fields and in the corporate world. There have also been innovations in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Feedback that is delivered more frequently than an annual evaluation appears to be beneficial in academic libraries as well. An extensive review of academic library performance appraisal systems by Stilling et al (2018) found that library leaders with feedback systems that contain an annual evaluation and additional feedback opportunities, rated the effectiveness of their feedback system's ability to create changes in the behavior of individual librarians, aid individual librarians in achieving job goals, and aid the library in achieving its overall organizational goals, at a statistically significant higher rate than library leaders with feedback systems that contain only an annual evaluation.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Feedback that is delivered more frequently than an annual evaluation appears to be beneficial in academic libraries as well. An extensive review of academic library performance appraisal systems by Stilling et al (2018) found that library leaders with feedback systems that contain an annual evaluation and additional feedback opportunities, rated the effectiveness of their feedback system's ability to create changes in the behavior of individual librarians, aid individual librarians in achieving job goals, and aid the library in achieving its overall organizational goals, at a statistically significant higher rate than library leaders with feedback systems that contain only an annual evaluation.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Dalam konteks ini, para manajer harus menilai kinerja karyawan, yang menjadi dasar untuk memutuskan tahapan apa yang harus diambil berikutnya. Penilaian kinerja menjadi perangkat dasar bagi terjalinnya komunikasi dan kesepahaman antara atasan-bawahan di berbagai jenis tempat kerja [2].…”
Section: Metodeunclassified
“…In this respect, the GESR database project aims at facilitating communication between the GCC countries' academic affairs and linking databases in universities, institutions and research centres (Stilling et al, 2018). This will help to make a high progress in databases, higher education institutions and research centres in the GCC.…”
Section: Introductionmentioning
confidence: 99%